Antithrombotic effects of saratin on human atherosclerotic plaques - Vilahur, Gemma; Duran, Xavier; Juan-Babot, Oriol; Casaní, Laura; Badimon, Lina (Thrombosis and Haemostasis, 2004)
Platelets play a primary role in thrombus formation after plaque rupture. Platelets recognize the exposed collagen via Von Willebrand factor (VWF) and become activated. Saratin, an inhibitor of the VWF-dependent binding of platelets to collagen, may reduce the thrombotic risk associated to atherosclerosis. Our objective was to evaluate the antithrombotic effects of local treatment with saratin on human atherosclerotic lesions. Thrombus formation was assessed by the deposition of 111Inplatelets on different human atherosclerotic lesions under three local shear conditions (800,1700 and 3400/s) with blood derived from catheterized pigs. Human atherosclerotic lesions were locally treated with saratin (30 µg/ml) at 37ºC for 5 min and placed in the chamber. Under stenotic shear conditions of 800/s, saratin significantly (p<0.05) reduced platelet deposition triggered by human denuded vessel wall (44%), fatty streaks (47%), severely damaged vessel (50%) and atherosclerotic plaque (57%). Thrombus characterization by immunohistochemistry showed also a reduction in fibrin deposition in treated vessels. These results suggest that the local site-specific treatment with saratin inhibits atherosclerotic plaque thrombogenicity at haemodynamic conditions typical of moderately stenotic coronary arteries.
Keywords: Von Willebrand Factor; collagen; saratin; platelets; thrombosis